2013
DOI: 10.1177/1941406413482972
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Enhanced Tablet Computers to Assess Children’s Food Frequency From Migrant Farmworker Mothers

Abstract: This study sought to improve data collection in children’s food frequency surveys for non-English speaking immigrant/migrant farmworker mothers using audio-enhanced tablet computers (ATCs). We hypothesized that by using technological adaptations, we would be able to improve data capture and therefore reduce lost surveys. This Food Frequency Questionnaire (FFQ), a paper-based dietary assessment tool, was adapted for ATCs and assessed consumption of 66 food items asking 3 questions for each food item: frequency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Finally, we established that farmworkers were willing and able to fully participate in mHealth programs to increase PPE use. Others have previously suggested that as technology becomes increasingly familiar to farmworkers, that mHealth approaches/services have tremendous potential to provide access to a wide range of their health care needs [ 9 - 11 ]. In the future, mHealth interventions like ¡Protéjase!…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we established that farmworkers were willing and able to fully participate in mHealth programs to increase PPE use. Others have previously suggested that as technology becomes increasingly familiar to farmworkers, that mHealth approaches/services have tremendous potential to provide access to a wide range of their health care needs [ 9 - 11 ]. In the future, mHealth interventions like ¡Protéjase!…”
Section: Discussionmentioning
confidence: 99%
“…Intervention strategies such as the use of mHealth (broadly defined as the use of mobile and wireless devices to improve health, health services, and health research) present a unique and viable intervention platform to improve PPE use. Moreover, there is preliminary evidence that Mexican and Latino farmworkers are likely to have mobile phones and are willing to receive health information in a mHealth format [ 9 - 11 ]. However, utilizing a mHealth approach for pesticide safety among a Mexican farmworker population has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of instruments showed adequate reliability, and the use of audio-enhanced PDAs and tablet computers in data collection was well received and resulted in good data quality. 21,22 Nursing research conducted in the rural community brings challenges in logistics. To keep travel expenses on budget, reasonably close migrant camps were scheduled on consecutive days and housing accommodations in rural areas needed to be found and paid.…”
Section: Discussionmentioning
confidence: 99%
“…The mother-reported children’s food frequency surveys were administered via audio-enhanced tablet computers or paper format. 22 Reports on data quality from the use of audio-enhanced PDAs and from the audio-enhanced tablet computers are reported elsewhere. 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…All translated documents then need to be translated back into the original language, compared for differences, and corrections made. Survey questions with audio-enhanced voice files on tablets have demonstrated good data quality, and using voice files to ‘speak’ to participants decreases the number of bilingual research team members needed at data collection sites (Kilanowski & Trapl, 2010; Kilanowski, Trapl, & Kofron, 2013). Depending on the sensitivity of the data collected, an additional consideration with consent forms is obtaining a Certificate of Confidentiality (COC).…”
mentioning
confidence: 99%